Navigating the New Normal: Adapting Online and Distance Learning in the Post-Pandemic Era - Simone Nomie Sato; Emilia Condes Moreno; Alejandro Rubio-Zarapuz; Athanasios A. Dalamitros; Rodrigo Yañez-Sepulveda; Jose Francisco Tornero-Aguilera; Vicente Javier Clemente-Suárez (Education Sciences, 2023)
This review examines the transformation of educational practices to online and distance learning during the COVID-19 pandemic. It specifically focuses on the challenges, innovative approaches, and successes of this transition, emphasizing the integration of educational technology, student well-being, and teacher development. The COVID-19 pandemic has significantly transformed the educational landscape, necessitating a rapid shift to online and distance learning. This review has highlighted key strategies and innovations in online teaching, emphasizing the importance of engaging, adaptable, and inclusive educational practices. It underscores the need for continuous professional development for educators, the integration of advanced technological tools, and the importance of prioritizing student well-being and academic success in digital environments. As we move forward, the insights gathered from this experience will be invaluable in shaping a resilient and dynamic educational framework that is well suited for the post-pandemic era, focusing on inclusivity, engagement, and the effective use of technology to enhance learning experiences.